Chronic cough in children: diagnostic problems and management at the stage of primary medical care - S.O. Mokia-Serbina; S.O. Sheiko; T.V. Litvinova; N.I. Zabolotnya (Zdorovʹe Rebenka, 2025)
Background. Chronic cough in children is one of the most common symptoms in outpatient and hospital practice. It is this complaint that becomes the main reason for parents of children to seek medical help. The purpose was to consider the problem of chronic cough in the practice of a primary care physician from the point of view of modern ideas about etiology, pathogenesis and approach to treatment. Materials and methods. To write the article, materials from the British Thoracic Society, the American College of Chest Physicians, and the European Respiratory Society guidelines on the diagnosis and treatment of chronic cough in adults and children were used. The search for information was carried out in the Scopus, PubMed, and Web of Science databases. Results. A sequence of diagnostic measures is proposed: detailed history taking, selection of studies that are clinically comparable with the history data and examination results. Attention is paid to the features of the clinical course of various phenotypes of chronic cough. It is noted that etiological and pathogenetic approaches are the most effective methods of treating chronic cough. The main directions of symptomatic treatment are substantiated. The issues of prescribing antitussive and mucoactive drugs are discussed. Conclusions. Chronic cough in children requires medical attention and observation, taking into account its connection with the future health of the child’s bronchopulmonary system.